Exposure to secondhand smoke at work: a survey of members of the Australian Liquor, Hospitality and Miscellaneous Workers Union - Melissa Cameron; Melanie Wakefield; Lisa Trotter; Graeme Inglis (Elsevier, 2003)
Abstract Objective: To measure workers' attitudes towards and experiences of exposure to secondhand smoke (SHS) in the workplace. Method: A stratified random sample of members from the Victorian Branch of the Australian Liquor, Hospitality and Miscellaneous Workers Union (LHMU) was interviewed by telephone in September 2001. Of the 1,078 respondents surveyed (77% response rate), hospitality workers comprised 49% of the sample, while the remainder comprised community services, property services and manufacturing workers. Results: Overall, 54% of union members were employed in workplaces that did not completely ban smoking and 34% reported being exposed to SHS during their typical working day. Workplaces with total smoking bans had a high level of compliance with these restrictions, with no workers in these settings indicating exposure to SHS at work. Compared with other workers, hospitality workers reported working in environments that had more permissive smoking policies. Consistent with this, 56% of hospitality workers said they were exposed to SHS during a typical day at work compared with 11% of other workers. Overall, 79% of workers expressed concern about exposure to SHS, including 66% of smokers. Compared with other workers, hospitality workers reported a higher level of concern about exposure to SHS at work. Conclusion: These findings provide evidence that many workers, and especially those employed in the hospitality sector, are exposed to SHS during their working day and are concerned about the effects of such exposure on their health. Implications: These findings indicate that workplace smoke‐free policies are effective in reducing worker exposure to SHS and demonstrate support for the extension of smoke‐free policies to hospitality workplaces.